Using a patient portal as a recruitment tool to diversify the pool of participants in COVID-19 vaccine clinical trials. Issue 4 (8th November 2022) - Yuh, Tiffany; Srivastava, Tuhina; Fiore, Danielle; Schmidt, Harald; Frank, Ian; Metzger, David; Momplaisir, Florence
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected racial/ethnic minorities in the United States, who are underrepresented in clinical trials. We assessed the feasibility of using the University of Pennsylvania Health System electronic health record patient portal to diversify the pool of participants in COVID-19 vaccine clinical trials. The patient portal was used to send invitations to eligible individuals living in zip codes with high rates of racial/ethnic minorities. The 5614 invited consisted of 96.7% black, 1.3% Hispanic/Latinx, and 1.5% white. The overall response rate was 5.4%, with lower response rates among Black (3.8%) and Hispanic/Latinx (9.6%) as compared to white individuals (91.6%). Among respondents, black individuals had lower rates of interest in participating (26.7%), as compared to white (65.8%) and Hispanic/Latinx (71.4%) individuals. Of 115 respondents who expressed interest, 9 enrolled in the clinical trial, which included 6 black, 3 white, and 1 Hispanic/Latinx. During phone outreach to nonresponders and decliners, common reasons for declining included mistrust of the COVID-19 vaccine, underlying health conditions, and logistical barriers to trial participation. Because of low rates of patient portal account activation and use, compounded with vaccine hesitancy, this method yielded a small number of interested individuals. Lay Summary: Racial and ethnic minorities are underrepresented in clinical research. They have also been the hardest hit by the coronavirus disease 2019 (COVID-19) pandemic. Therefore, it is important to ensure racial and ethnic minorities are adequately represented in COVID-19 vaccine clinical trials. In this way, we can ensure that the vaccines are safe and effective in these populations, which will help increase vaccine uptake in these hardest-hit groups. In a COVID-19 vaccine trial at our medical center, we attempted to diversify the racial/ethnic pool of participants by sending invitations through the electronic patient portal targeting those living in areas with high rates of racial/ethnic minorities. We found that low numbers of individuals responded to the message, particularly among black and Hispanic/Latinx individuals in comparison to white individuals. Of a total of 5614 invited patients, only 9 enrolled in the trial. Ultimately, because of low patient portal use, compounded with vaccine hesitancy, mistrust, and other barriers to participation in clinical research, this method of recruiting minorities through a patient portal was not fruitful. We must develop strategies to increase patient portal use among racial/ethnic minorities, improve patient portal messaging, and address concerns about vaccination and participation in research.